Praktik Manajemen Keuangan Keluarga dan Implikasinya Terhadap Keharmonisan Keluarga - Fauzaan Ahmad Nurkhofi; Moh. Makmun; Haris Hidayatulloh (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Family financial management is an essential aspect of achieving family harmony, particularly among families with significant economic and social responsibilities, such as teachers. This study aims to analyze the implementation of family financial management, identify the condition of family harmony, and examine the role of financial management in fostering harmonious family relationships among teachers at Madrasah Aliyah Negeri 6 Jombang. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving both civil servant (PNS) and government contract (PPPK) teachers. The data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that family financial management is implemented through financial planning, budgeting, prioritizing household needs, transparency in financial management, and joint decision-making between spouses. Family harmony is reflected in effective communication, mutual trust, openness, and the ability to resolve conflicts wisely. Effective financial management contributes to household economic stability, enables families to meet their needs, and minimizes the potential for financial conflicts. Therefore, family financial management plays a significant role in supporting and maintaining family harmony.